Project Based Assessment with a Phenomenon-Based Learning Approach on Achieving the Pancasila Student Profile in Elementary School - Widiana, I Wayan; Kristiantari, Maria Goreti Rini; Widiani, Ni Komang (Universitas Pendidikan Ganesha, 2023)
The Pancasila student profile is a description of the competencies that Indonesian students must have. This study aims to analyze the impact of project-based assessment with a phenomenon-based learning approach on achieving the Pancasila student profile in elementary school students. This research is experimental research using a quantitative approach. The research design used in this study was a nonequivalent post-test only control group design. The populations in this study were elementary school students spread across various regions, namely rural, suburban and urban areas. Determining the number of samples in this study was carried out using the Slovin formula with an error tolerance limit of 3%. Furthermore, sampling in this research was carried out using cluster random sampling techniques. Based on the results of the Independent Sample T-Test analysis using the IBM SPSS Statistics 21.0 for Windows program, a significance value (Sig. 2-tailed) was obtained of 0.000. Based on these results, it can be seen that the Sig. < 0.05. So, it can be concluded that H0 is rejected and Ha is accepted. In other words, there is a significant difference in the achievement of the Pancasila student profile in the group that was given treatment in the form of a project-based assessment with a phenomenon-based learning approach and those who were not treated in the form of a project-based assessment with a phenomenon-based learning approach. Thus, the use of project-based assessment with a phenomenon-based learning approach is effective in increasing students' achievement of the Pancasila Student Profile indicators.